DESIGN, DEVELOPMENT AND OPTIMIZATION OF MOUTH DISSOLVING TABLET OF AMBRISENTAN USING DESIGN EXPERT SOFTWARE - MANKAR, S. D.; SATPUTE, AJAY; SIDDHESHWAR, S. S.; BHAWAR, S. B.; DIGHE, S. B. (International Journal of Applied Pharmaceutics, 2023)
Objective: The rationale of the current work is to design, develop and optimize of mouth dissolving tablet of ambrisentan to treat hypertension. Methods: Sodium starch glycolate and crospovidone were used as the super disintegrants in the direct compression method to create nine ambrisentan mouth-dissolving tablet formulations. Wetting time, drug content, in vitro disintegration time, dispersion time, and dissolution time were all assessed for the produced formulations. Results: Based on the results obtained, formulation F6 containing 30 mg of crospovidone exhibited good wetting time, dispersion time, disintegration time and drug release. The hardness of formulations AS1 to AS9 was found to be in the range of 2.5 to 3.11 Kg/cm2. The friability of formulations AS1 to AS9 was found to be less than 1%. A water absorption ratio was performed for ensuring the moisture sorption and water uptake properties of super disintegrants. The in vitro drug release of formulation AS6 containing a concentration of Crospovidone 30 mg, shows 91.30% drug release respectively at the end of 12 min. Conclusion: The mouth-dissolving tablets of ambrisentan were successfully designed, developed, and fabricated. It can be reasonably concluded that the AS6 batch of mouth-dissolving tablets of ambrisentan with 30 mg of crospovidone exhibited maximum cumulative drug release in 12 min.